Prioritizing Human-Centric and Social Life Cycle Assessment (S-LCA) Criteria in Industry 4.0 and 5.0 Technologies Using an Integrated AHP-TOPSIS-VIKOR Framework - Aikhuele, Daniel Osezua (Risk Assessment and Management Decisions, 2025)
The fast growth of digital technologies in Industry 4.0 brought monumental developments in automation systems and efficiency rates. However, the recent shift to Industry 5.0 has brough its own demands, this time the integration of human-centered, sustainable, and resilient approach into the manufacturing environment. This research establishes a strong Multi-Criteria Decision-Making (MCDM) framework to meet this imperative knowledge gap in sustainable evaluation of innovative manufacturing and digital technologies. A thorough comparison of ten criteria of sustainability to environmental, economic as well as social indicators was conducted via Analytic Hierarchy Process (AHP) in order to determine their weighted importance. The process of evaluation included the application of Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) and VIKOR method to a seven-emerging technology decision-making matrix. Tech C maintained the highest degree of sustainability among any of the alternatives with the TOPSIS value of 0.8106 and recorded a zero VIKOR value. The identical rankings being reached by both TOPSIS and VIKOR methods confirm the credibility of the model. The research provides a technical assessment method which allows stakeholders to select technologies based on Industry 5.0 philosophies through a framework that can be used for pragmatic and repetitive application.